Clinical risk factors predictive of thrombotic stroke with large cerebral infarction - Worapot Rojsanga; Kittisak Sawanyawisuth; Verajit Chotmongkol; Somsak Tiamkao; Kannikar Kongbonkiat; Narongrit Kasemsap (MDPI AG, 2019)
Large cerebral infarctions have high morbidity and mortality. Patients with large cerebral infarctions may have recurrent ischemia as high as 8.1% within 7 days; highest among other types of strokes. Data regarding risk factors for large cerebral infarction in Asian populations are still scant. All adult (age ≥15 years old) patients with the diagnosis of thrombotic ischemic stroke who were treated at Srinagarind Hospital, Khon Kaen University, Thailand from January 2012 to December 2013 were studied. Large cerebral infarctions are defined by clinical criteria of having cerebral cortical impairment, brain stem or cerebellar dysfunction with infarction sizes of more than 1.5 cm. The association of various stroke risk factors and large infarction strokes were calculated using multiple logistic regression analysis. There were 276 thrombotic stroke patients who met the study criteria; classified as large cerebral infarctions in 59 patients (21.38%) and small cerebral infarctions in 217 patients (78.62%). Baseline characteristics and risk factors for stroke were comparable between both groups. The large cerebral infarction group had a significantly larger proportions of right internal carotid artery stenosis, plaques on the left side, left internal carotid artery stenosis, and internal carotid artery stenosis at any side than the small cerebral infarction group. Among various stroke risk factors, only internal carotid artery stenosis at any side was the only significant factor associated with large cerebral infarction with an adjusted odds ratio of 11.14 (95% CI: 3.46, 35.82). In conclusion, significant internal carotid artery stenosis is associated with large cerebral infarction.